Effect of SiO2 dispersion on chlorine-induced high temperature corrosion of HVAF-sprayed NiCrMo coating - Sadeghimeresht, Esmaeil; Markocsan, Nicolaie; Hussain, Tanvir; Huhtakangas, Matti; Joshi, Shrikant (National Association of Corrosion Engineers, 2018)
NiCrMo coatings with and without dispersed SiO2 were deposited using high velocity air-fuel (HVAF) technique. Thermogravimetric experiments were conducted in 5% O2+500 vppm HCl+N2 with and without a KCl deposit at 600 °C for up to 168 h. The SiO2-containing coating showed lower weight change due to formation of a protective and adherent Cr-rich oxide scale. SiO2 decelerated short-circuit diffusion of Cr3+ through scale’s defects, e.g., vacancies, and promoted the selective oxidation of Cr to form the protective Cr-rich oxide scale. Furthermore, the presence of SiO2 led to less subsurface depletion of Cr in the coating, and accordingly less corrosion of the substrate. The formed corrosion product on the SiO2-free coating was highly porous, non-adherent, and thick.